Preparation method and application of organic-inorganic composite solid electrolyte membrane

The method of preparing organic-inorganic composite solid electrolyte membranes without solvents has solved the impact of solvent residue on electrolyte stability, achieved higher electrochemical performance and safer production process, and is suitable for the application of semi-solid lithium-ion batteries.

CN119905675APending Publication Date: 2025-04-29SHANDONG SACRED SUN POWER SOURCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510110665.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing solid electrolyte preparation process relies on solvents, resulting in the residual solvent adversely affecting the stability of the electrolyte and poses environmental and health risks.

Method used

Using a solvent-free preparation method, the organic solid electrolyte, inorganic solid electrolyte and lithium salt are heated and melted to form a slurry, and then coated on the surface of the substrate, cooled and dried to obtain an organic-inorganic composite solid electrolyte membrane.

Benefits of technology

It eliminates the negative impact of solvents on electrolyte stability, reduces environmental and health hazards, and improves electrochemical performance, and is suitable for the application of semi-solid lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005256575140000071
    Figure BDA0005256575140000071
  • Figure BDA0005256575140000081
    Figure BDA0005256575140000081
  • Figure HDA0005256575150000011
    Figure HDA0005256575150000011
Patent Text Reader

Abstract

The invention provides a preparation method of an organic-inorganic composite solid electrolyte membrane, which comprises the following steps: A) heating and melting an organic solid electrolyte, an inorganic solid electrolyte and a lithium salt to obtain slurry; and B) coating the surface of a substrate with the slurry, cooling, drying and stripping to obtain the organic-inorganic composite solid electrolyte membrane. According to the method for preparing the organic-inorganic composite solid electrolyte membrane in the solvent-free manner, the composite solid electrolyte membrane is prepared under the solvent-free condition, so that the problem of dependence on the solvent is solved, and the adverse effect of the existence of the residual solvent on the stability of the electrolyte is avoided. Meanwhile, the obvious negative effects of evaporation of toxic organic solvents on the environment and personal health are reduced. Compared with a single-phase electrolyte, the composite solid electrolyte membrane prepared by the invention has more excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state lithium batteries, and in particular relates to a preparation method and application of an organic-inorganic composite solid electrolyte membrane. Background Art

[0002] With the continuous depletion of non-renewable resources on the earth and the deepening of the energy crisis, the demand for energy storage and conversion equipment is becoming increasingly urgent. In order to meet this demand, battery devices with high energy conversion efficiency and high energy density are indispensable. As an important carrier for energy storage and utilization, lithium batteries have gradually matured in technology after decades of development. However, lithium batteries have problems such as uncontrollable growth of lithium dendrites and leakage of toxic and flammable liquid electrolytes during use, making it difficult to ensure safety during operation. Solid electrolytes have high mechanical strength and do not contain flowing liquids, which can effectively alleviate the safety problems caused by lithium metal anodes. In addition, solid electrolytes bring better electrochemical and thermal stability to batteries, thereby extending the cycle life of batteries and broadening the application scenarios of lithium metal batteries. Solid electrolytes act as both separators and liquid electrolytes, and have higher theoretical energy density than traditional lithium batteries. For these reasons, solid electrolytes represent a promising research area for further exploring the potential of lithium batteries.

[0003] Solid electrolytes are mainly divided into two categories according to the type of materials: organic solid electrolytes and inorganic solid electrolytes. Among them, organic solid electrolytes refer to polymer electrolytes, and inorganic solid electrolytes mainly include sulfide electrolytes, chloride electrolytes and oxide electrolytes. Sulfides and chlorides cannot be mass-produced at present due to their complex synthesis process, low yield and high production environment requirements. The brittleness and fragility of oxides make it difficult to apply to flexible batteries. In addition, they form a poor contact interface between the electrolyte and the electrode, resulting in high interface resistance and poor cycle performance. In contrast, polymer electrolytes have lower conductivity than inorganic electrolytes at room temperature, but have good flexible mechanical properties. Due to the limitations of material properties, it is difficult to achieve the ideal requirements of solid electrolytes with single-phase electrolytes. Composite solid electrolytes are composed of two or more different materials. Composite electrolytes can provide the advantages of multiple materials at the same time. Through different composite methods, the advantages of various materials can be integrated into the most essential part of the battery in a specific form. Polymer-oxide composites can combine the characteristics of flexibility and high ionic conductivity, and are regarded as ideal material systems that can obtain both high conductivity and satisfactory mechanical properties.

[0004] However, these experiments all use solvent dispersion as a means of modification and preparation, which requires multiple steps such as dissolution, mixing, and drying, increasing the difficulty and cost of production. In addition, during the preparation process, the evaporation of large amounts of toxic organic solvents has significant negative impacts on the environment and personal health. Most importantly, the current production process cannot exclude the influence of residual solvent molecules, and the presence of residual solvents may have an adverse effect on the stability of the electrolyte.

[0005] In summary, finding a method to reduce the presence of residual solvents and eliminate the influence of solvents on electrolyte stability is an urgent problem that technicians in this field need to solve. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing an organic-inorganic composite solid electrolyte membrane and its application. The preparation method provided by the present invention avoids the use of solvents and eliminates the influence of solvents on the stability of the electrolyte.

[0007] The present invention provides a method for preparing an organic-inorganic composite solid electrolyte membrane, comprising the following steps:

[0008] A) heating and melting an organic solid electrolyte, an inorganic solid electrolyte and a lithium salt to obtain a slurry;

[0009] B) coating the slurry on the surface of a substrate, and peeling it off after cooling and drying to obtain an organic-inorganic composite solid electrolyte membrane.

[0010] Preferably, step A) comprises:

[0011] A1) heating and melting an organic solid electrolyte, adding a lithium salt, heating and stirring to dissolve, and obtaining a slurry;

[0012] A2) adding an inorganic solid electrolyte to the slurry, heating and stirring to dissolve, to obtain a slurry.

[0013] Preferably, the organic solid electrolyte includes at least one of succinonitrile and polyethylene oxide.

[0014] Preferably, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), and lithium hexafluorophosphate.

[0015] Preferably, the inorganic solid electrolyte includes one or more of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, and tantalum-doped lithium lanthanum zirconium oxide (LLZTO).

[0016] Preferably, the mass ratio of the lithium salt to the organic solid electrolyte is (0.5-0.8):1.

[0017] Preferably, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte is (0.1-0.2):1.

[0018] Preferably, in step A2), the time for heating, stirring and dissolving is 2 to 8 hours.

[0019] Preferably, in step B), the cooling time is 6 to 12 hours, the drying temperature is 50 to 80° C., and the drying time is 4 to 10 hours.

[0020] The present invention also provides a semi-solid lithium ion battery, comprising the organic-inorganic composite solid electrolyte membrane prepared by the above preparation method.

[0021] Compared with the prior art, the present invention provides a method for preparing an organic-inorganic composite solid electrolyte membrane, comprising the following steps: A) heating and melting an organic solid electrolyte, an inorganic solid electrolyte and a lithium salt to obtain a slurry; B) coating the slurry on the surface of a substrate, cooling and drying, and then peeling off to obtain an organic-inorganic composite solid electrolyte membrane. In the method for preparing an organic-inorganic composite solid electrolyte membrane without solvent provided by the present invention, a composite solid electrolyte membrane is prepared under solvent-free conditions, which solves the problem of dependence on solvents and the adverse effect of the presence of residual solvents on the stability of the electrolyte. At the same time, the evaporation of toxic organic solvents has a significant negative impact on the environment and personal health. The composite solid electrolyte membrane prepared by the present invention has better electrochemical properties than single-phase electrolytes. In addition, the thickness of the composite solid electrolyte membrane prepared by the present invention affects the electrochemical properties of the solid-state battery. By adjusting the different thicknesses of the solid electrolyte membrane, a solid-state battery with optimal performance is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Impedance diagrams of button-type semi-solid batteries prepared in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing an organic-inorganic composite solid electrolyte membrane, comprising the following steps:

[0024] A) heating and melting an organic solid electrolyte, an inorganic solid electrolyte and a lithium salt to obtain a slurry;

[0025] B) coating the slurry on the surface of a substrate, and peeling it off after cooling and drying to obtain an organic-inorganic composite solid electrolyte membrane.

[0026] In some embodiments of the present invention, step A) comprises:

[0027] A1) heating and melting an organic solid electrolyte, adding a lithium salt, heating and stirring to dissolve, and obtaining a slurry;

[0028] A2) adding an inorganic solid electrolyte to the slurry, heating and stirring to dissolve, to obtain a slurry.

[0029] Specifically, in a glove box, the organic solid electrolyte is heated to melt, and then the heating is continued, and lithium salt is added to heat, stir and dissolve to obtain slurry.

[0030] Wherein, the organic solid electrolyte includes at least one of succinonitrile and polyethylene oxide.

[0031] The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide (LITFSI), lithium bis(oxalatoborate) (LiBOB), and lithium hexafluorophosphate (LiPF6).

[0032] The mass ratio of the lithium salt to the organic solid electrolyte is (0.5-0.8):1, and can be 0.5:1, 0.55:1, 0.6:1, 0.625:1, 0.7:1, 0.725:1, 0.8:1, or any value between (0.5-0.8):1.

[0033] Then, an inorganic solid electrolyte is added to the slurry, and heating and stirring are continued to obtain a slurry.

[0034] The inorganic solid electrolyte includes one or more of lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), and tantalum-doped lithium lanthanum zirconium oxide (LLZTO).

[0035] The mass ratio of the inorganic solid electrolyte to the organic solid electrolyte is (0.1-0.2):1, and can be 0.1:1, 0.125:1, 0.13:1, 0.145:1, 0.16:1, 0.2:1, or any value between (0.1-0.2):1.

[0036] The time for the heating, stirring and dissolving is 2 to 8 hours, and the temperature for the heating, stirring and dissolving is higher than the melting point of the organic solid electrolyte and lower than the boiling point of the organic solid electrolyte.

[0037] Then, the slurry is coated on the surface of the substrate, and is peeled off after cooling and drying to obtain an organic-inorganic composite solid electrolyte membrane.

[0038] In the present invention, the substrate is selected from a polytetrafluoroethylene plate, a polyethylene plate or a polypropylene plate. The present invention has no particular limitation on the coating method, and any coating method known to those skilled in the art can be used. In the present invention, it is preferred to use a film applicator to scrape the slurry onto the substrate.

[0039] After coating, cooling is performed, and the cooling time is 6 to 12 hours, which can be 6, 7, 8, 9, 10, 11, 12, or any value between 6 and 12 hours.

[0040] After cooling, drying is performed. The present invention has no particular restrictions on the drying method. Preferably, the present invention uses a vacuum oven for drying. The drying temperature is 50 to 80°C, which can be 50, 60, 70, 80, or any value between 50 and 80°C, wherein it is necessary to ensure that the drying temperature is lower than the melting point of the organic solid electrolyte. The drying time is 4 to 10 hours, which can be 4, 5, 6, 7, 8, 9, 10, or any value between 4 and 10 hours.

[0041] After drying, the organic-inorganic composite solid electrolyte membrane is peeled off from the substrate, and the sample is punched out using a puncher;

[0042] Select solid electrolyte membranes with uniform texture and assemble semi-solid lithium-ion batteries.

[0043] The present invention also provides an organic-inorganic composite solid electrolyte membrane prepared by the above preparation method, wherein the thickness of the organic-inorganic composite solid electrolyte membrane is 20 to 300 μm, which can be 20, 50, 100, 150, 200, 250, 300, or any value between 20 and 300 μm.

[0044] The present invention also provides a semi-solid lithium ion battery, comprising the organic-inorganic composite solid electrolyte membrane prepared by the above preparation method.

[0045] The present invention aims at the problem of the influence of residual solvent on the stability of electrolyte, and proposes a method for preparing a solvent-free organic-inorganic composite solid electrolyte membrane and its application in semi-solid lithium-ion batteries. The preparation method is to uniformly mix the organic solid electrolyte and lithium salt into a molten fluid by heating in a certain dehumidified environment, then add the inorganic solid electrolyte and continue to stir until the inorganic solid electrolyte is completely dissolved, then scrape the molten fluid on the substrate, cool it to obtain the organic-inorganic composite solid electrolyte membrane, and finally assemble it into a button-type semi-solid lithium-ion battery. The method is green and efficient, simple to operate, and helps to promote the industrial application of solid electrolytes and solid lithium batteries.

[0046] In order to further understand the present invention, the preparation method and application of the organic-inorganic composite solid electrolyte membrane provided by the present invention are described below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0047] Example 1

[0048] The instruments and chemicals used in the process of the present invention include: a tablet puncher, a beaker, a volumetric flask, a precision balance (0.0001 g), tweezers, a drying oven, a battery testing system, an electrochemical workstation, a glove box, a tablet press, positive and negative battery shells, a gasket, a shrapnel, a stirrer, succinonitrile, polyethylene oxide, lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), and tantalum-doped lithium lanthanum zirconium oxide (LLZTO).

[0049] A method for preparing an organic-inorganic composite solid electrolyte membrane without solvent and its application in a semi-solid lithium-ion battery. The specific preparation and characterization steps are as follows:

[0050] In a glove box, heat 30 g of succinonitrile to 70°C, add molten succinonitrile and 21 g of lithium bis(trifluoromethanesulfonyl imide) (LITFSI) into a volumetric flask, make up to volume, and continue heating and stirring to completely dissolve LITFSI;

[0051] 4.5 g of LLZTO was added to the above volumetric flask, heated and stirred at 70°C for 6 h to obtain a uniformly distributed slurry, which was then coated on a polytetrafluoroethylene plate with a film applicator, cooled in a glove box for 6 h, then removed from the glove box, and dried in a vacuum oven at 60°C for 10 h to obtain an organic-inorganic composite solid electrolyte membrane;

[0052] The solid electrolyte membrane was peeled off from the polytetrafluoroethylene plate, and the sample was punched out using a puncher;

[0053] Select a solid electrolyte membrane with uniform texture and assemble a button-type semi-solid lithium-ion battery as follows:

[0054] 1. Place the positive electrode shell with the opening facing upward on the glass plate;

[0055] 2. Use tweezers to place the stainless steel sheet into the positive electrode shell, with the positive electrode sheet in the middle;

[0056] 3. Clamp the solid electrolyte membrane and cover it with a stainless steel sheet;

[0057] 4. Clamp the stainless steel sheet and place it in the middle of the diaphragm;

[0058] 5. Clamp the spring and place it on the stainless steel, aligning it strictly;

[0059] 6. Use tweezers to grab the negative electrode shell cover.

[0060] Example 2

[0061] The difference between Example 2 and Example 1 is that in step 1, the organic solid electrolyte is polyethylene oxide, and the heating temperature is 90° C. In step 2, the heating and stirring temperature is 90° C.

[0062] Example 3

[0063] The difference between Example 3 and Example 1 is that in step 2, LATP is selected as the inorganic solid electrolyte.

[0064] Example 4.

[0065] The difference between Example 4 and Example 1 is that the thickness of the solid electrolyte membrane of Example 4 after cooling is 20 μm.

[0066] Comparative Example 1

[0067] The solid electrolyte membrane was obtained using a dry process. The specific implementation steps are as follows: in a glove box, 30 g of succinonitrile, 21 g of LITFSI and 4.5 g of LLZTO were ground together to obtain a paste mixture, which was then hot-pressed at 100°C to obtain a solid electrolyte membrane with a thickness of about 50 μm.

[0068] Comparative Example 2

[0069] The solid electrolyte membrane was obtained using an electrospinning machine. The specific implementation steps are as follows: in a glove box, 30 g of succinonitrile was heated to 90°C, and molten succinonitrile and 21 g of LITFSI were added to a volumetric flask, the volume was fixed, and heating and stirring were continued to completely dissolve LITFSI;

[0070] 4.5 g of LLZTO was added to the above volumetric flask, heated and stirred at 90°C for 6 h to obtain a uniformly distributed slurry. An electrospinning machine was used to obtain an electrospun fiber membrane, which was then dried in a vacuum oven at 60°C for 10 h to obtain an organic-inorganic composite solid electrolyte membrane with a thickness of 50 μm.

[0071] Comparative Example 3

[0072] The solid electrolyte membrane was obtained using a twin-screw extruder. The specific implementation steps are as follows: in a glove box, 30 g of succinonitrile was heated to 90°C, molten succinonitrile and 21 g of lithium bis(trifluoromethanesulfonyl)imide (LITFSI) were added to a volumetric flask, the volume was fixed, and heating and stirring were continued to completely dissolve LITFSI;

[0073] 4.5 g of LLZTO was added to the above volumetric flask, heated and stirred at 90°C for 6 h to obtain a mixed slurry. The mixed material was then sheared at a speed of 100 kg / h in a twin-screw extruder to obtain a mixed solution, which was then cast into a film through the extruder die; and then dried in a vacuum oven at 60°C for 10 h to obtain an organic-inorganic composite solid electrolyte membrane with a thickness of 50 μm.

[0074] Comparative Example 4

[0075] In a glove box, 30 g of polyethylene oxide was added to 100 mL of dimethylacetamide and stirred on a magnetic stirrer for 3 h. When the polyethylene oxide particles were completely dissolved, 4.5 g of LLZO powder was added to the uniform solution, and the mixed suspension containing the LLZO powder was magnetically stirred. When the LLZO powder was evenly dispersed in the mixed solution, 21 g of LITFSI was added to the mixed solution, and magnetically stirred again for 2 h to completely dissolve LITFSI to obtain a uniform slurry containing PEO / LLZO.

[0076] The slurry was coated on a polytetrafluoroethylene plate with a film applicator, cooled in a glove box for 6 hours, then removed from the glove box and dried in a vacuum oven at 60° C. for 10 hours to obtain an organic-inorganic composite solid electrolyte membrane.

[0077] The performance of the organic-inorganic composite solid electrolyte membrane prepared in the above examples and comparative examples was tested, and the testing method was as follows:

[0078] (1) Impedance test.

[0079] The solid electrolyte membrane was assembled into a "stainless steel sheet / / solid electrolyte membrane / / stainless steel sheet" battery for impedance spectrum testing to obtain the impedance R. Electrochemical workstation setting parameters: test frequency 10 -2 ~10 6 HZ, amplitude is 5mV.

[0080] (2) Ionic conductivity.

[0081] The ionic conductivity is calculated according to formula (1):

[0082] σ = L / (R×S) Formula (1);

[0083] Wherein, L is the thickness of the solid electrolyte membrane, R is the impedance obtained from the impedance spectrum, and S is the effective contact area between the electrode and the solid electrolyte membrane.

[0084] (3) Lithium ion migration number.

[0085] The solid electrolyte membrane was assembled into a "lithium sheet / / solid electrolyte membrane / / lithium sheet" battery for lithium ion migration number test. The lithium ion migration number of the plasma membrane, the electrochemical workstation setting parameters: test voltage 0.01V, test time 14400s. Lithium ion migration number (t + ) is calculated according to formula (2):

[0086] t + =[(ΔV-I0R 0 e1 ) / (ΔV-I S R S e1 )] formula (2);

[0087] Among them, I0 and I S are the initial current and the stable current after polarization is completed, R 0 e1 and R S e1 are the initial interface impedance and the interface impedance after polarization is completed, respectively, and ΔV is the set constant voltage of 10mV.

[0088] Test results see Figure 1 Compared with Table 1, Figure 1 Impedance diagrams of button-type semi-solid batteries prepared in the embodiments of the present invention and the comparative examples.

[0089] Table 1 Basic properties of semi-solid electrolyte membranes of Examples 1 to 4 and Comparative Examples 1 to 4

[0090]

[0091]

[0092] The test results in Table 1 show that Example 2, i.e., the composite solid electrolyte membrane prepared by polyethylene oxide and LLZTO, can obtain higher ionic conductivity and mechanical properties. Although the solid electrolyte membrane prepared by the dry process in Comparative Example 1 is simple to prepare, it has a high impedance, resulting in poor battery performance. In Comparative Example 2, although the solid electrolyte membrane obtained by the electrospinning machine has relatively good performance in all aspects, the electrospinning machine is expensive and complicated to operate. It is currently only used in the laboratory and is not suitable for large-scale production. In Comparative Example 3, the solid electrolyte membrane obtained by the twin-screw extruder has relatively general performance, and the thickness of the electrolyte membrane is uneven. In Comparative Example 4, although the use of organic solvents can slightly improve the ionic conductivity of the solid electrolyte membrane, the puncture strength and tensile strength of the solid electrolyte membrane prepared by the solvent method are lower than those of the solid electrolyte membrane prepared by the solvent-free method, and the use of the solvent method will cause the volatilization of the organic solvent, causing harm to personnel and environmental pollution.

[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an organic-inorganic composite solid electrolyte membrane, characterized in that: The following steps are involved: A) heating and melting an organic solid electrolyte, an inorganic solid electrolyte and a lithium salt to obtain a slurry; B) coating the slurry on the surface of a substrate, and peeling it off after cooling and drying to obtain an organic-inorganic composite solid electrolyte membrane.

2. The preparation method according to claim 1, characterized in that: Step A) comprises: A1) heating and melting an organic solid electrolyte, adding a lithium salt, heating and stirring to dissolve, and obtaining a slurry; A2) adding an inorganic solid electrolyte to the slurry, heating and stirring to dissolve, to obtain a slurry.

3. The preparation method according to claim 1, characterized in that: The organic solid electrolyte includes at least one of succinonitrile and polyethylene oxide.

4. The preparation method according to claim 1, characterized in that: The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), and lithium hexafluorophosphate.

5. The preparation method according to claim 1, characterized in that: The inorganic solid electrolyte includes one or more of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, and tantalum-doped lithium lanthanum zirconium oxide (LLZTO).

6. The preparation method according to claim 1, characterized in that: The mass ratio of the lithium salt to the organic solid electrolyte is (0.5-0.8):

1.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the inorganic solid electrolyte to the organic solid electrolyte is (0.1-0.2):

1.

8. The preparation method according to claim 2, characterized in that: In step A2), the heating, stirring and dissolving time is 2 to 8 hours.

9. The preparation method according to claim 1, characterized in that: In step B), the cooling time is 6 to 12 hours, the drying temperature is 50 to 80° C., and the drying time is 4 to 10 hours.

10. A semi-solid lithium ion battery, characterized in that: The invention comprises an organic-inorganic composite solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 9.